Il teatro e l’indagine sull’umano. L’attore moderno in scena... all’ombra di Diderot - Cecilia Uberti Foppa (Itinera, 2021)
Can we say that the 18th century philosophe Denis Diderot and his theses of theatrical aesthetics are still relevant and viable on the modern theatre stage? The article elaborates on our contemporaneity to try to give an answer to this question, creating questionnaires-interviews with four professional actors with questions related to the key themes of Diderot's theatrical and artistic aesthetics, encountering the incredible actuality of the Diderotian vision. The idea of the actor's profession is, in its true essence, an aesthetic idea, thus stimulating a philosophical reflection based on all the great concepts of this discipline, highlighted by the theoretical and practical thought of Diderot and now investigated by the theatrical practice of contemporary actors: body, gestures, genius, interpretation, communication, expression.